2016
DOI: 10.5433/1679-0359.2016v37n3p1355
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells promote augmented response of endogenous neural stem cells in spinal cord injury of rats

Abstract: Traumatic spinal cord injury results in severe neurological deficits, mostly irreversible. The cell therapy represents a strategy for treatment particularly with the use of stem cells with satisfactory results in several experimental models. The aim of the study was to compare the treatment of spinal cord injury (SCI) with and without mesenchymal stem cells (MSC), to investigate whether MSCs migrate and/or remain at the site of injury, and to analyze the effects of MSCs on inflammation, astrocytic reactivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…However, MSC transplantation attenuated astrocytosis in the CPZ model. In keeping with our study, Araujo et al (2016) showed that damages to the CNS elevated the intensity astrocytic marker (GFAP). Explained as fibrillar reactive astrocytosis, this is related to hyperplasia and hypertrophy of astrocytes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, MSC transplantation attenuated astrocytosis in the CPZ model. In keeping with our study, Araujo et al (2016) showed that damages to the CNS elevated the intensity astrocytic marker (GFAP). Explained as fibrillar reactive astrocytosis, this is related to hyperplasia and hypertrophy of astrocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Explained as fibrillar reactive astrocytosis, this is related to hyperplasia and hypertrophy of astrocytes. The reactive astrocytes derived from the glial scar accumulates around the lesion, forming a physical barrier and an inhibitory environment for axonal regeneration and remyelination (Araujo et al, 2016). The significant reduction was observed in astrocytes of the MSC‐treated animals suggests that MSC can undermine the astrocytes response and mitigate the effects of scar tissue formation on providing a suitable environment for remyelination.…”
Section: Discussionmentioning
confidence: 99%